THE MOTIVATION OF SURABAYA SOCIETY ON SWITCHING MOBILE PHONE NUMBER - Krisnadiputra, Kevin (University of Surabaya, 2014)
Trend of increasing mobile phone number churn rate makes several mobile phone number providers concern to anticipating the issue. This journal emphasizes on the motivation of Surabaya society on switching mobile phone number. The purpose of this study is to explore the peopleâs motivation on switching mobile phone number due to increasing churn rate thatâs happening in Indonesia. Information from the interview are analyzed based on Vroomâs expectancy theory to break down the human motivation based on the three elements. The result shows that there are basic motivations from the expectancy of people to switch their mobile phone number and it is supported by the simplicity to change mobile phone number. The knowledge from this research might be usefull for mobile phone number providers to know the basic motivation of their customer.